2018
DOI: 10.1038/gim.2018.27
|View full text |Cite
|
Sign up to set email alerts
|

Targeted genetic analysis in a large cohort of familial and sporadic cases of aneurysm or dissection of the thoracic aorta

Abstract: PurposeThoracic aortic aneurysm/aortic dissection (TAAD) is a disorder with highly variable age of onset and phenotype. We sought to determine the prevalence of pathogenic variants in TAAD-associated genes in a mixed cohort of sporadic and familial TAAD patients and identify relevant genotype-phenotype relationships. MethodsWe used a targeted PCR and next generation sequencing-based panel for genetic analysis of 15 TAAD associated genes in 1025 unrelated TAAD cases. ResultsWe identified 49 pathogenic or likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 40 publications
9
41
1
Order By: Relevance
“…9,10 Indeed, high or increased diagnostic yields were observed when patients with a positive family history, with early-onset aortic disease, or with a syndromic form of TAAD were included primarily. 9,10,13 In our study, however, the diagnostic yield was not increased in patients with a positive family history. Furthermore, in three previous studies the cohorts mainly included individuals with an unambiguous TAAD phenotype; however diagnostic yields were not consistent.…”
Section: Diagnostic Yieldcontrasting
confidence: 77%
See 2 more Smart Citations
“…9,10 Indeed, high or increased diagnostic yields were observed when patients with a positive family history, with early-onset aortic disease, or with a syndromic form of TAAD were included primarily. 9,10,13 In our study, however, the diagnostic yield was not increased in patients with a positive family history. Furthermore, in three previous studies the cohorts mainly included individuals with an unambiguous TAAD phenotype; however diagnostic yields were not consistent.…”
Section: Diagnostic Yieldcontrasting
confidence: 77%
“…Several studies on NGS applications for the molecular diagnosis of TAAD have been reported. [9][10][11][12][13][14][15][16] Taking into account only PV and LPV, the diagnostic yields were documented as 3.9% (21 genes in 102 patients analyzed), 12 4.9% (15 genes in 1025 patients analyzed), 13 8.1% (21 genes in 810 patients), 16 10.3% (10 genes in 175 patients analyzed), 11 13% (7 genes in 264 patients analyzed), 15 18.6% (11 genes in 70 patients analyzed), 14 27% (14 genes in 55 patients analyzed), 10 and 35.3% (10 genes in 51 patients analyzed). 9 In our subcohort of 71 patients with the initial diagnosis of TAAD, 12 individuals had a PV or LPV resulting in a diagnostic yield of 16.9%.…”
Section: Diagnostic Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant risk factors for a pathogenic variant in patients with thoracic aortic dissection or rupture were young age (<50 years old), no history of hypertension, but strong family history of aortic aneurysm, dissection or rupture (especially involving mother, siblings and children) with estimated odds ratios ranging from 5.1 for affected siblings to 6.0 for affected children (Table 4). This is in agreement with a recent study in familial and sporadic cases of aneruysm or dissection of the thoracic aorta which demonstrated a significantly increased probability of harboring a pathogenic or likely pathogenic variant in cases which were syndromic, young (age <50), or with a known or probable family history 26 . Patients with pathogenic variants in TGFBR1/2 (Loeys-Dietz syndrome), FBN1 (Marfan syndrome), and MYH11 have a higher risk of aortic dissection and suffer more complications from aortic dissection, including death 6 .…”
Section: Discussionsupporting
confidence: 93%
“…Here, we established, optimized, and combined functional analyses of the adult zebrafish heart using echocardiography and MRI with a morphological characterization of the cardiac compartments and adjacent vessels using µ-CT. As a proof-of-concept, we examined alk5a/tgfbr1 mutants as TGFBR1 genetic variants in humans have been associated with aortic aneurysms and diseases of the great vessels, the diagnosis of which is most often recognized in young adults (Loeys et al, 2005;Loeys et al, 2006;Matyas et al, 2006;Weerakkody et al, 2018;Camerota et al, 2019). We show that the use of this multimodal preclinical imaging strategy allows for a robust dissection of adult zebrafish cardiac phenotypes, even in the presence of high variability between samples of the same genotype.…”
Section: Introductionmentioning
confidence: 99%